The cytokine milieu compromises functional capacity of tumor-infiltrating plasmacytoid dendritic cells in HPV-negative but not in HPV-positive HNSCC - Koucký, Vladimír; Hladíková, Kamila; Táborská, Eliška; Bouček, Jan; Grega, Marek; Špíšek, Radek; Fialová, Anna (Cancer immunology, immunotherapy, 2021)
Plasmacytoid dendritic cells (pDCs) are the most potent type I interferon-producing cells and play an important role in antiviral immunity. Tumor-infiltrating pDCs were shown to be predominantly pro-tumorigenic, with reduced ability to produce interferon alpha (IFNα) and confirmed capacity to prime regulatory T cells (Tregs) by the ICOS/ICOS-L pathway. Because a significant number of HNSCCs are induced by human papillomaviruses and show markedly different immune profiles than non-virally induced tumors, we compared the phenotype and functional capacity of HNSCC-infiltrating pDCs to the HPV status of the tumor. We observed a reduced capacity of pDCs to produce IFNα upon toll-like receptor activation in HPV-negative samples and a rather uncompromised functionality in HPV-associated tumors. Additionally, supernatants from non-virally induced but not HPV-associated tumor cell suspensions significantly inhibited IFNα production by peripheral blood-derived pDCs. We identified IL-10 and TNFα as the soluble pDC-suppressive factors with the highest variability between HPV-negative and HPV-positive tumor-derived supernatants. Additionally, we observed a positive correlation of tumor-infiltrating pDCs with Tregs in HPV-negative samples but not in virally induced tumors. Overall, our study indicates that the immunosuppressive cytokine milieu rich in IL-10 and TNFα in HPV-negative but not in HPV-positive HNSCC significantly affects the functional capacity of tumor-infiltrating pDCs, and such dysfunctional pDCs may further support the immunosuppressive tumor microenvironment by promoting the expansion of Tregs in the tumor tissue.
Keywords: Interferon alpha; studie případů a kontrol; cytokiny; Tumor Microenvironment; Humans; virová transformace buněk; infekce papilomavirem; dlaždicobuněčné karcinomy hlavy a krku; Cytokines; Plasmacytoid dendritic cells; Papillomavirus Infections; Squamous Cell Carcinoma of Head and Neck; Human papillomavirus; nádorové mikroprostředí; Head and neck cancer; Cell Transformation, Viral; biologické markery; Disease Susceptibility; Gene Expression; interferon alfa; dendritické buňky; náchylnost k nemoci; lidé; T-lymfocyty - podskupiny; Case-Control Studies; T-Lymphocytes, Regulatory; Biomarkers; Interferon-alpha; regulační T-lymfocyty; exprese genu; T-Lymphocyte Subsets; Dendritic Cells